Fully human anti-CD39 antibody potently inhibits ATPase activity in cancer cells via uncompetitive allosteric mechanism. Issue 1 (1st January 2020) - Spatola, Bradley N.; Lerner, Alana G.; Wong, Clifford; dela Cruz, Tracy; Welch, Megan; Fung, Wanchi; Kovalenko, Maria; Losenkova, Karolina; Yegutkin, Gennady G.; Beers, Courtney; Corbin, John; Soros, Vanessa B.
ABSTRACT: The extracellular ATP/adenosine axis in the tumor microenvironment (TME) has emerged as an important immune-regulatory pathway. Nucleoside triphosphate diphosphohydrolase-1 (NTPDase1), otherwise known as CD39, is highly expressed in the TME, both on infiltrating immune cells and tumor cells across a broad set of cancer indications. CD39 processes pro-inflammatory extracellular ATP to ADP and AMP, which is then processed by Ecto-5ʹ-nucleotidase/CD73 to immunosuppressive adenosine. Directly inhibiting the enzymatic function of CD39 via an antibody has the potential to unleash an immune-mediated anti-tumor response via two mechanisms: 1) increasing the availability of immunostimulatory extracellular ATP released by damaged and/or dying cells, and 2) reducing the generation and accumulation of suppressive adenosine within the TME. Tizona Therapeutics has engineered a novel first-in-class fully human anti-CD39 antibody, TTX-030, that directly inhibits CD39 ATPase enzymatic function with sub-nanomolar potency. Further characterization of the mechanism of inhibition by TTX-030 using CD39 + human melanoma cell line SK-MEL-28 revealed an uncompetitive allosteric mechanism (α < 1). The uncompetitive mechanism of action enables TTX-030 to inhibit CD39 at the elevated ATP concentrations reported in the TME. Maximal inhibition of cellular CD39 ATPase velocity was 85%, which compares favorably to results reported for antibody inhibitors to other enzyme targets. The allosteric mechanism of TTX-030 was confirmed via mapping the epitope to a region of CD39 distant from its active site, which suggests possible models for how potent inhibition is achieved. In summary, TTX-030 is a potent allosteric inhibitor of CD39 ATPase activity that is currently being evaluated in clinical trials for cancer therapy.